Remyelination-Promoting DNA Aptamer Conjugate Myaptavin-3064 Binds to Adult Oligodendrocytes In Vitro - Mahboubeh Fereidan-Esfahani; Wei Ying Yue; Brandon Wilbanks; Aaron J. Johnson; Arthur E. Warrington; Charles L. Howe; Moses Rodriguez; Louis J. Maher (MDPI AG, 2020)
We previously applied Systematic Evolution of Ligands by EXponential enrichment (SELEX) technology to identify myelin-specific DNA aptamers, using crude mouse central nervous system myelin as bait. This selection identified a 40-nucleotide aptamer (LJM-3064). Multiple biotinylated LJM-3064 molecules were conjugated to a streptavidin core to mimic a multimeric immunoglobulin M (IgM) antibody, generating 3064-BS-streptavidin (Myaptavin-3064). We previously showed that Myaptavin-3064 induces remyelination in the Theiler's murine encephalomyelitis virus (TMEV) model of chronic spinal cord demyelination. While details of target binding and the mechanism of action remain unclear, we hypothesized that Myaptavin-3064 induces remyelination by binding to oligodendrocytes (OLs). We now report the results of binding assays using the human oligodendroglioma (HOG) cell line, applying both flow cytometry and immunocytochemistry (IC) to assay aptamer conjugate binding to cells. IC assays were applied to compare aptamer conjugate binding to primary embryonic mouse mixed cortical cultures and primary adult rat mixed glial cultures. We show that Myaptavin-3064 binds to HOG cells, with increased binding upon differentiation. In contrast, a negative control aptamer conjugate, 3060-BS, which did not promote central nervous system (CNS) remyelination, does not bind to HOG cells. Myaptavin-3064 did not bind to lung (L2) or kidney (BHK) cell lines. Total internal reflection fluorescence (TIRF) imaging indicates that Myaptavin-3064 binds at the cell membrane of live cells. In addition to HOG cells, Myaptavin-3064 binds to adult rat OLs, but not to embryonic mouse mixed cortical cultures. These data support the hypothesis that Myaptavin-3064 binds to a surface molecule on both rodent and human OLs in a manner that triggers a remyelination signal pathway.